PENGARUH SELF-EFFICACY DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI PADA SMA NEGERI PATI KOTA DI KABUPATEN PATI - Wijaningsih, 12.5202.0199; Fauzan, Muhamad (Jurnal Mahasiswa Pasca Sarjana, 2015)
This reasearch is aimed to test the influence of self-efficacy and professional competence toward the performance of the teacher in the moderation of the organization culture. The spesific objective of this research is to test the role of the cultural organization moderating the influence of self-efficacy and professioanl competence towards the teacher performance. The benefit of this reserch are explaining andÂ  expanding the previous research about the role of the cultural organization moderating the influence of self-efficacy and professional competency towards the teacher performance. This research using a population of the state senior high schoolâs teacher in Pati subdistrict, Pati regency as many as one hundred and forty five teachers. The sample collection technique in this research by the census method. The analysis technique used is regression quasi moderation model. Based on the result of the research self-efficacy has a negative influence toward the teacher performance, professional competence has a positive and significant influence toward the teacher performance, cultural organization has a positive and significant toward the teacher performance, cultural organization debilitating the influence of self-efficacy toward the teacher performance, cultural organization strengthen the influence of the professional competence toward the teacher performance. Keywords: self-efficacy, professional competence, cultural organization, teacher performance